Strong convergence of modified noor iteration in CAT(0) spaces - Asawathep Cuntavepanit (2018)
We prove a strong convergence theorem for the modified Noor iterations in the framework of CAT(0) spaces. Our results extend and improve the corresponding results of X. Qin, Y. Su and M. Shang, T. H. Kim and H. K. Xu and S. Saejung and some others. © 2014 Iranian Mathematical Society.